Metagenomics: novel enzymes from non-culturable microbes. Issue 21 (4th October 2017) - Berini, Francesca; Casciello, Carmine; Marcone, Giorgia Letizia; Marinelli, Flavia
Abstract: In the transition to the post-petroleum economy, there is a growing demand for novel enzymes with high process performances to replace traditional chemistry with a more 'green' approach. To date, microorganisms encompass the richest source of industrial biocatalysts, but the Earth-living microbiota remains largely untapped by using traditional isolation and cultivation methods. Metagenomics, which is culture independent, represents a powerful tool for discovering novel enzymes from unculturable microorganisms. Herein, we summarize the variety of approaches adopted for mining environmental DNA and, based on a systematic literature review, we provide a comprehensive list of 332 industrially relevant enzymes discovered from metagenomes within the last three years. Abstract : Metagenomics is a powerful tool for identifying novel microbial biocatalysts.